1998
DOI: 10.1094/phyto.1998.88.2.144
|View full text |Cite
|
Sign up to set email alerts
|

A Major Gene for Powdery Mildew Resistance Transferred to Common Wheat from Wild Einkorn Wheat

Abstract: A major gene for resistance to wheat powdery mildew (Blumeria graminis f. sp. tritici = Erysiphe graminis f. sp. tritici) has been successfully transferred into hexaploid common wheat (Triticum aestivum, 2n = 6x = 42, AABBDD) from wild einkorn wheat (Triticum monococcum subsp. aegilopoides, 2n = 2x = 14, AA). NC96BGTA5 is a germ plasm line with the pedigree Saluda x 3/PI427662. The response patterns for powdery mildew resistance in NC96BGTA5 were tested with 30 differential isolates of B. graminis f. sp. triti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 18 publications
1
50
0
Order By: Relevance
“…In order to improve resistance, wheat (Triticum aestivum L.) had been crossed with its related genera (Jiang et al 1993), such as Aegilops, Elytrigia, Secale, Haynaldia, and related species of Triticum, for instance, T. boeoticum, T. dicoccoides, T. carthlicum and T. timopheevii, which represent a reservoir of genes for resistance to multiple diseases. Intergeneric and interspecific crosses have resulted in the transfer of desirable fungal resistance into wheat; for example, powdery mildew resistance genes, Pm7, Pm8, Pm17, and Pm20 originated from Secale (McIntosh et al 2011); Pm12, Pm13, Pm19, Pm29, Pm32, Pm34, and Pm35 originated from Aegilops (Miranda et al 2007); Pm21 originated from Haynaldia (Cao et al 2011); Pm40 and Pm43 originated from Elytrigia (He et al 2009); Pm4b and Pm33 originated from T. carthlicum (Zhu et al 2005); Pm25 originated from T. boeoticum (Shi et al 1998); and Pm6, Pm27, and Pm37 originated from T. timopheevii (Perugini et al 2008). All provide race-specific resistance to powdery mildew.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve resistance, wheat (Triticum aestivum L.) had been crossed with its related genera (Jiang et al 1993), such as Aegilops, Elytrigia, Secale, Haynaldia, and related species of Triticum, for instance, T. boeoticum, T. dicoccoides, T. carthlicum and T. timopheevii, which represent a reservoir of genes for resistance to multiple diseases. Intergeneric and interspecific crosses have resulted in the transfer of desirable fungal resistance into wheat; for example, powdery mildew resistance genes, Pm7, Pm8, Pm17, and Pm20 originated from Secale (McIntosh et al 2011); Pm12, Pm13, Pm19, Pm29, Pm32, Pm34, and Pm35 originated from Aegilops (Miranda et al 2007); Pm21 originated from Haynaldia (Cao et al 2011); Pm40 and Pm43 originated from Elytrigia (He et al 2009); Pm4b and Pm33 originated from T. carthlicum (Zhu et al 2005); Pm25 originated from T. boeoticum (Shi et al 1998); and Pm6, Pm27, and Pm37 originated from T. timopheevii (Perugini et al 2008). All provide race-specific resistance to powdery mildew.…”
Section: Introductionmentioning
confidence: 99%
“…RFLP, RAPD and AFLP markers linked to wheat powdery mildew resistance genes Pm1 (Hartl et al 1995(Hartl et al , 1999Hu et al 1997), Pm2 (Ma et al 1994), Pm3 (Hartl et al 1993), Pm4 (Ma et al 1994), Pm6 (Tao et al 2000), Pm8 (Hsam et al 2000), Pm12 (Jia et al 1996), Pm13 (Donini et al 1995;Cenci et al 1999), Pm18 (Hartl et al 1993), Pm21 (Qi et al 1996), Pm24 (Huang et al 2000b), Pm25 (Shi et al 1998), Pm26 (Rong et al 2000), Pm27 (Järve et al 2000), Pm29 (Zeller et al 2002) and Pm30 (Liu et al 2002) have been identified. Microsatellites, also termed simple sequence repeats (SSRs) as a new type of genetic marker reveal a much higher polymorphism in wheat than any other marker system (Plaschke et al 1995;Huang et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Pm3 (a total of ten alleles, Pm3a to Pm3j) and Pm 25 were located on chromosome 1AS (Hartl et al 2000;Shi et al 1998 Kong et al 1999;Heun and Friebe 1990). Until to now, no any powdery mildew resistance gene has been mapped on wheat chromosome 1B.…”
Section: Discussionmentioning
confidence: 99%